Advances in Selective Electrochemical Oxidation of 5‐Hydroxymethylfurfural to Produce High‐Value Chemicals. Issue 4 (8th December 2022) - Guo, Lei; Zhang, Xiaoxue; Gan, Li; Pan, Lun; Shi, Chengxiang; Huang, Zhen‐Feng; Zhang, Xiangwen; Zou, Ji‐Jun
Abstract: The conversion of biomass is a favorable alternative to the fossil energy route to solve the energy crisis and environmental pollution. As one of the most versatile platform compounds, 5‐hydroxymethylfural (HMF) can be transformed to various value‐added chemicals via electrolysis combining with renewable energy. Here, the recent advances in electrochemical oxidation of HMF, from reaction mechanism to reactor design are reviewed. First, the reaction mechanism and pathway are summarized systematically. Second, the parameters easy to be ignored are emphasized and discussed. Then, the electrocatalysts are reviewed comprehensively for different products and the reactors are introduced. Finally, future efforts on exploring reaction mechanism, electrocatalysts, and reactor are prospected. This review provides a deeper understanding of mechanism for electrochemical oxidation of HMF, the design of electrocatalyst and reactor, which is expected to promote the economical and efficient electrochemical conversion of biomass for industrial applications. Abstract : This review provides a deeper understanding of mechanism for electrochemical oxidation of 5‐hydroxymethylfurfural (HMF), the design of electrocatalyst and reactor, and points out the possible important development orientation, which is expected to promote the economical and efficient electrochemical conversion of biomass for industrial applications.